DINAMIKA INTELEKTUAL ISLAM DI KALIMANTAN SELATAN: STUDI GENEALOGI, REFERENSI, DAN PRODUK PEMIKIRAN - Rahmadi, Rahmadi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2012)
This paper tries to explore the intelectual Islamic dynamic in South Kalimantan throughthe studies on many influences that become the genealogic root of Islam in this region,and then through the religious literatures that referenced by the intelectual of religiouselite and the tipology of thoughts product that emerged for more than two centuries.Here, the writer uses the history of social-intelectual approach with based on the writtentext. This writing tells us that the genealogical root, intelectual reference, and the tipologyof religious thought which was producted actually part of the trend of intelectual muslimdynamic which commonly spreaded in Nusantara and Southeast Asia.